Writer identify, self-other relations and writing strategies in the narratives of Nigerian second language learners - Bello, Mohammed (2019)
Language use is important in understanding the identity of the author in a written discourse. Given that the author produces the writing for the other, an in-depth understanding of how students display identities to relate to others in writing is needed. Previous studies mainly examined how identity is displayed in spoken discourse. However, little is known about the construction of writer‟s identity and that of the other in second language writing among Nigerian students. Thus, this study explores how public secondary school students in Nigeria narrate their junior year experiences. It also examines the strategies used in constructing ideas and connections with the other in writing. The study seeks to understand how identity and self-other relations are embedded in the students‟ written language as they communicate their ideas. Data were collected using purposive sampling comprising forty-five students‟ written narratives, transcriptions of in-depth interviews, notes from classroom observations and interpreted through a discourse analytical approach. The findings reveal varied ways the self relates to others in writing, that is, through loan words, nouns, pronouns and words that convey appreciation, salutation, and care in their narratives. The study creates awareness of not only self as the writer but also about the relations with the other and the strategies in writing. It contributes to the understanding of writer identity, the strategies used and the relevance of others in writing. It also reinforces the need for educators to give attention to second language writing ability and see writing as not only the product. Rather, writing speaks volumes about the author‟s voice which relates to identity, culture and social background. Future research should explore how identity and self-other construction are reflected in other written genres, specifically, in academic writing, given the cultural identity of the author, style, positioning and knowledge about writing in English.